Schouten Bracket of Holomorphic Tensors of a Kahlerian Manifold - Jorga Ibrahim (Journal of Mathematical and Fundamental Sciences, 1974)
Abstract. It is shown that the Schouten bracket of holomorphic tensors of a compact kahlerian manifold W defines a structure of graded complex Lie algebra on the space of holomorphic tensors of the manifold. We obtain an important proposition which generalizes a wellknown result of Lichnerowicz [6,7].Ringkasan. Kita perlihatkan bahwa "Schouten bracket" dari pada tensor-tensot holomorph milik suatu manifold kahler yang kompak W mendefinisikan suatu struktur "graded complex Lie algebra" pada ruang tensor-tenso holomorph dari pada manifold tersebut. Disini diperoleh suatu proposisi yang penting yang memperluas sebuah hasil yang terkenal dari Lichnerowicz [6,7].